Oceanographic drivers of winter habitat use in Cassin's Auklets. Issue 3 (21st January 2020) - Johns, Michael E.; Warzybok, Pete; Jahncke, Jaime; Lindberg, Mark; Breed, Greg A.
Abstract: Reduced prey abundance and severe weather can lead to a greater risk of mortality for seabirds during the non‐breeding winter months. Resource patterns in some regions are shifting and becoming more variable in relation to past conditions, potentially further impacting survival and carryover to the breeding season. As animal tracking technologies and methods to analyze movement data have advanced, it has become increasingly feasible to draw fine‐scale inference about how environmental variation affects foraging behavior and habitat use of seabirds during this critical period. Here, we used archival light‐sensing tags to evaluate how interannual variation in oceanography affected the winter distribution of Cassin's Auklets from Southeast Farallon Island, California. Thirty‐five out of 93 geolocators deployed from 2015 to 2017 were recovered and successfully recorded light‐level data, from which geographic positions were estimated. Step‐selection functions were applied to identify environmental covariates that best explained winter movement decisions and habitat use, revealing Cassin's Auklets dispersed farther from the colony during a winter with warm SST anomalies, but remained more centralized near the breeding colony during two average winters. Movement patterns were driven by avoidance of areas with higher sea surface temperatures and possible limits of dispersal from the breeding colony, and selection for areas with well‐defined mesoscale fronts and cooler surface waters. Through multiple years of tagging and the application of step‐selection functions, a robust and widely applied approach for analyzing animal movement in terrestrial species, we show how interannual differences in the movement patterns of a small seabird are driven by oceanographic variability across years. Understanding the winter habitat use of seabirds can help inform changes in population structure and measures of reproductive success, aiding managers in determining potential causes of breeding failures.